The Lived Body in Schizophrenia: Transition from Basic Self-Disorders to Full-Blown Psychosis - Irarrázaval, Leonor (Frontiers in Psychiatry, 2015)
This paper provides the results of a phenomenological study of patients with schizophrenia during their first psychiatric hospitalization. The study aims at clarify aspects related to the diagnosis of schizophrenia and to reach a greater understanding of the illness, with a view to contribute to prevention and psychotherapeutic intervention models. First, the paper offers a description of the patients’ “disembodiment” manifested in acute phases of schizophrenia. Second, it presents a description of the subjective anomalies that may be considered as disorders of “ipseity” or of pre-reflexive self-awareness. Third, the description is extended to encompass secondary disturbances to processes of establishing consensual intersubjectivity that lead to difficulties in shared communication practices and a progressive withdrawal from the intersubjective world. The conclusion states that a structural element, a key part of the personal processes involved in schizophrenia, is the diminishment of self-presence in experience, which manifests on both individual and social levels.